Analysis of view of stakeholders on temporary accommodation after disasters in Serbia - Brankov, Borjan (Arhitektura i urbanizam, 2018)
Natural disasters are increasingly causing damage or devastation of the settlements. In recent years, the number and intensity of natural hazards in Serbia has increased. As a result, there is a growing need for temporary accommodation of the vulnerable population. The paper through the survey, conducted in the period from April to June 2017, examines the characteristics of the housing in which the surveyed population currently live and their view regarding the temporary accommodation. The first survey (60 surveyed residents from the territory of Serbia) deals with the population who were in temporary accommodation and potentially vulnerable population which were not. Simultaneously paper conducted a survey of representatives of 11 organizations involved in the issue of temporary accommodation (NGOs, humanitarian and development organizations and academic institutions). The analysis of the results of the conducted surveys shows the differences in the current accommodation in which the population live and the one in which they would like to be or they were after disaster. Discussion of the obtained results highlights the importance of the spatial elements such as window surfaces, living area, existence of additional spaces etc. The result of this paper is to determine the opinions and desires of the vulnerable population and to set directions and recommendations for future research. The quality of temporary housing can contribute to the normalization of life activities that result in improved social and housing conditions and a sense of belonging to the community, not marginalization and social exclusion